Harnessing knowledge dynamics : principled organizational knowing & learning - Nissen, Mark E., 1958- (Hershey, PA : IRM Press, 2006)
'This book provides 30 principles on which to base the most important decisions and actions in an organization pertaining to knowledge management' -- Provided by publisher.
Includes bibliographical references (p. 232-239) and index.
Keywords: Knowledge management; Organizational learning